2010
DOI: 10.1104/pp.109.148189
|View full text |Cite
|
Sign up to set email alerts
|

S-Glycoprotein-Like Protein Regulates Defense Responses in Nicotiana Plants against Ralstonia solanacearum      

Abstract: RsRGA4 (for Ralstonia solanacearum-responsive gene A4) encodes a polypeptide similar to S-locus glycoprotein (SGP) from Brassica rapa and SGP-like proteins from Ipomoea trifida and Medicago truncatula. Therefore, we designated RsRGA4 as NtSGLP (for Nicotiana tabacum SGP-like protein) and NbSGLP (its Nicotiana benthamiana ortholog). NbSGLP is expressed in root, leaf, petal, gynoecium, and stamen. Expression of NbSGLP was strongly induced by inoculation with an avirulent strain of R. solanacearum (Rs8107) and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…In addition, the roles of SGT1 and SlALC1, two key genes in the coronatine/jasmonate (JA) pathway, and inducible NO synthase (iNOS) in resistance against P. syringae have been uncovered [107]. In tobacco plants, the important roles of NbHSP90c-1, NbHSP70c-1, WIPK, and SIPK genes in non-host resistance to P. cichorii, and SGLP in resistance against Ralstonia solanacearum, have been demonstrated by VIGS [108][109][110]. In a study searching for genes required for defense responses against Xanthomonas campestris in plants, Bs4, SGT1, CaCYP450A, CaRING1, SlMKK2 and SlMPK2 genes have been characterized [111][112][113][114][115].…”
Section: Genes Involved In the Defense Response To Pathogens Insectsmentioning
confidence: 99%
“…In addition, the roles of SGT1 and SlALC1, two key genes in the coronatine/jasmonate (JA) pathway, and inducible NO synthase (iNOS) in resistance against P. syringae have been uncovered [107]. In tobacco plants, the important roles of NbHSP90c-1, NbHSP70c-1, WIPK, and SIPK genes in non-host resistance to P. cichorii, and SGLP in resistance against Ralstonia solanacearum, have been demonstrated by VIGS [108][109][110]. In a study searching for genes required for defense responses against Xanthomonas campestris in plants, Bs4, SGT1, CaCYP450A, CaRING1, SlMKK2 and SlMPK2 genes have been characterized [111][112][113][114][115].…”
Section: Genes Involved In the Defense Response To Pathogens Insectsmentioning
confidence: 99%
“…26 P. syringae pv tabaci 6605 was cultured in PY medium containing 20 µg/ mL rifampicin. 27 Purification of TβL was performed according to the method described by Tomas et al 28 Bacterial suspension, l-methionine sulfoximine (MSX; Funakoshi) and TβL were infiltrated into N. benthamiana leaves as described previously. 9 Isolation of RNA and cDNA synthesis Total RNA was isolated from N. benthamiana leaves with RNAiso (Takara), and RNA samples were treated with DNase I (RNase-free; Takara) to degrade contaminating genomic DNA as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…13 Ralstonia solanacearum strain OE1-1 and the corresponding hrpY (encoding Hrp pilus)-mutant of R. solanacearum strain OE1-1 was cultured in PY medium containing 20 mg/mL rifampicin or 20 mg/mL kanamycin, respectively. 12 Bacterial suspension were infiltrated into N. benthamiana leaves as described previously. 13 …”
Section: Methodsmentioning
confidence: 99%
“…7 We previously reported that cellular components, such as asparagine-rich protein, S-glycoprotein-like protein and translationally controlled tumor protein, have important role in regulation of plant defenses against R. solanacearum. [10][11][12] In addition, our previous report showed that molecular chaperon, Nbshsp17, has a crucial role in regulation of plant defenses, suggesting involvement of molecular chaperons and co-chaperons in plant and R. solanacearum interaction. 13 In this study, we focused on Hsp90, RAR1 and SGT1.…”
Section: Introductionmentioning
confidence: 99%